Profesionalitas Guru Sekolah Dasar dalam menghadapi Ragam Karakteristik Belajar - Zahid Zufar At Thaariq; Lindawati Lindawati; Ryandini Dwi Puspita (EduBasic Journal: Jurnal Pendidikan Dasar, 2020)
This research aimed to review the professionalism of teachers in the face of the learning characters of elementary school students. In the learning process, a teacher's role was critical. Thus, teachers need to be professional in managing learning in the classroom in terms of media management, models and learning resources. This study used mixed methods approach between qualitative and quantitative. This research used online poll instruments and spread to 24 respondents. Respondents were taken from teachers at the elementary school level. The steps in this study were (1) the formulation of the problem (2) looking for the theory foundation, (3) the poll instrument formulation, (4) the distribution of polls, (5) data presentation and (6) drawing conclusions and suggestions. The results revealed that the elementary school teacher had a variety of methods and action in the learning such as the use of discussion, demonstration, lecturing and problem solving methods with a variety of specific reasons. The character of learners became the first consideration on implementing the variety of methods and action. So, the learning process tended to become more varied. The expectation of this research could capture teacher’s performance and give basis to improve the teachers’ profesionalism in the classrooms teaching and learning process.